THE MORTALITY BY DISEASES IN LATYIA IEDZĪVOTĀJU MIRSTĪBA NO SLIMĪBĀM LATVIJĀ (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
In Latvia the mortality of population in Latvia is very high. In some districts the mortality is several times higher than the birth rate. This leads to a negative population increment. One of the causes of death is the heart — circulation diseases. The mortality in different regions varies. Investigation the economic, cultural, geographical ethnic and social situation are used to solve the reasons of the unfavourable demographic situation. Special attention has been carried out to investigate the mortality rate and the indicators of adaptation to the market economy in various rural regions in Latvia. On X-axis is the mortality of residents from heart-circulation diseases in different regions of Latvia, on the Y-axis - various indicators of education, economic, social and cultural development.It has been shown that in various rural regions in Latvia with different mortality of heart-circulation diseases there are differences with the various indicators of economic life and education level. In regions with higher percentage of residents with higher or secondary education the mortality by heart-circulation diseases are lower. This coincides also with higher pre school children enrolment in pre school establishments, and with lower enrolment in auxiliary and trade schools. In these regions children enter presumably schools with Russian instruction language. These regions are located in the eastern part of Latvia - Latgale, were the Russian speaking population has increased in the occupation period of Latvia not only as a result of migration of other Soviet Republics, but also as a lack of adequate school politics. Thus for example in the district of Daugavpils the most population have Latvian citizenship, however they enter the schools with Russian instructional language. The prestige of Latvian language is increasing in the latest period, presumably as a result of the universities in Daugavpils and Rēzekne. As a consequence the children enter more schools with the Latvian instructional language. Not only the mortality from heart - circulation diseases is increased in theses regions of Latvia, but also the total mortality. The birth rate is decreased and the increment of population has a negative sign (the population is dying out with a rate, which in Latgle is higher than 1% per year. High mortality coincides with lower education and with lower success in economic activities. Between them is the lower yield of cow’s milk and agriculture output and the road quality. It should be mentioned that the fertility of soil in the districts of higher mortality is lower than in the districts of lower incidence of mortality by heart - circulation diseases. Various economic activities in regions with high ore low mortality of heart and circulation diseases were very different. Also predisposition to some other diseases, as diseases of gastrointestinal tract and suddenly poisoning and mortality as a result of external factors has been increased. That served to get motivation that all efforts to improve education including pre school children establishments are really important for Latvia.In Latvia during the post-war time pre school establishments increased each year. At the school year 1988/89 the enrolment size was 140000, but it dropped very rapidly after 1990 because the schools were very dear in comparison with the earnings ofparents. Also the decrease ofpopulation has been observed in all districts of Latvia.